2008
DOI: 10.1194/jlr.m800158-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxy-ceramide synthesis by ceramide synthase family: enzymatic basis for the preference of FA chain length

Abstract: Ceramide is unusually abundant in epidermal stratum corneum and is important for permeability barrier function. Ceramides in epidermis also comprise an unusual variety, including 2-hydroxy (a-hydroxy)-ceramide. Six mammalian ceramide synthase/longevity assurance homologue (CerS/LASS) family members have been identified as synthases responsible for ceramide (CER) production. We reveal here that of the six, CerS3/LASS3 mRNA is the most predominantly expressed in keratinocytes. Moreover, its expression is increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 36 publications
(75 reference statements)
3
62
1
Order By: Relevance
“…The control siRNA and siRNAs for CERS2, CERS4, and CERS5 were purchased from Qiagen and have been described previously (21). The nucleotide sequences of ELOVL1 siRNA were 5â€Č-CCUGUACUACGGAUUAU-CUGC-3â€Č (sense) and 5â€Č-AGAUAAUCCGUAGUACAGGUA-3â€Č (antisense), and the corresponding duplex siRNA was purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…The control siRNA and siRNAs for CERS2, CERS4, and CERS5 were purchased from Qiagen and have been described previously (21). The nucleotide sequences of ELOVL1 siRNA were 5â€Č-CCUGUACUACGGAUUAU-CUGC-3â€Č (sense) and 5â€Č-AGAUAAUCCGUAGUACAGGUA-3â€Č (antisense), and the corresponding duplex siRNA was purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…No enzyme that produces sphingolipid bases with two double bonds has yet been identified in any organism; however, the Drosophila genome contains a single homolog of fatty acid 2-hydroxylase (FA2H). This enzyme generates the a-hydroxy fatty acids present in some vertebrate sphingolipids (Maldonado et al, 2008;Mizutani et al, 2008;Uchida et al, 2007). To determine whether it has a similar activity in Drosophila, we altered its levels and measured the resulting changes in sphingolipid fatty acid hydroxylation.…”
Section: Sterol Depletion Alters Abundance Of Specific Sphingolipid Vmentioning
confidence: 99%
“…Northern blot analyses by two groups showed that FA2H is expressed in many organs (20,21). In a recent study, Mizushima et al (38) reported that all six isoforms of ceramide synthase (LASS/CerS) can synthesize hFA-ceramide. In our unpublished studies, we have yet to encounter any biological samples (tissues, cells, or serum) with no FA2H or hFA, although their abundance could be diminutively low in some specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to C 16 fatty acid, many other fatty acids (C 14 -C 34 ) can be used. The N-acylation step is catalyzed by any of the six isoforms of ceramide synthase (38). GSL, glycosphingolipid; SM, sphingomyelin.…”
Section: Thymidine Incorporation Assaymentioning
confidence: 99%